The cross‐sectional, longitudinal, and transitional associations between perceived support and suicidal ideation and behavior in late adolescence and emerging adulthood: Adjacent‐category logit models. Issue 5 (13th June 2022) - Nestor, Bridget A.; Liu, Qimin; Tran, Tiffany; Cole, David A.
Abstract: Introduction: Suicidal ideation (SI) and attempts (SA) are prevalent in late adolescence and emerging adulthood. Prior research has identified perceived support as a correlate of SI and SA. Less is known, though, about the role of perceived support in differentiating among suicidal outcomes and between the incremental escalation of suicidal outcomes from SI to SA to serious suicide attempts (SSA). Method: Using ordinal regression, we used Wave 1 and 2 data from the National Longitudinal Study of Adolescent to Adult Health ( N = 4500; 53% female; M age = 16.6; 12% Hispanic) to examine cross‐sectional, longitudinal, and transitional models of perceived support and suicidality. Results: Cross‐sectional results indicated that youths with higher perceived support were less likely to have suicidal ideation. Longitudinal results showed that youths with higher perceived support at Wave 1 were less likely to have suicidal ideation or serious suicide attempts at Wave 2. Transitional model results revealed that higher perceived support at Wave 1 was negatively associated with escalation in suicidal outcomes from Wave 1 to 2. Conclusion: We discuss findings in the context of theories of suicide and discuss implications for suicide risk identification, intervention, and prevention efforts in late adolescence and emerging adulthood.